Obesity, sedentarism and TMD-pain in adolescents - Jordani, Paula C. [UNESP]; Campi, Letícia B. [UNESP]; Braido, Guilherme V. V. [UNESP]; Fernandes, Giovana [UNESP]; Visscher, Corine M.; Gonçalves, Daniela A. G. [UNESP] (Wiley, 2019)
Background: Obesity is a chronic and prevalent disorder, affecting individuals of all age. Previous evidence suggests that it is associated with some types of chronic pain, especially musculoskeletal pain. In addition, sedentarism is also associated with an increase of the inflammatory factors and chronic pain. So, we conducted a cross-sectional study to evaluate the association between obesity, sedentarism and the presence of TMD-pain in adolescents. Methods: Temporomandibular Disorders were classified according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). Obesity was assessed by the body mass index (BMI), bioimpedance (BIA), skinfold (triceps and subscapular) and circumferences (arm and abdominal). The level of physical activity was rated according to the instrument adopted by the Brazilian National School Health Survey. Descriptive statistics, univariate logistic regression and odds ratios (OR) with 95% confidence intervals (CI) were used to study the associations of interest. Results: The sample consisted of 690 individuals with a mean age of 12.7 (±0.76) years of whom 389 (56.4%) were girls. Of the total, 112 (16.2%) had TMD-pain, 110 (15.9%) were obese according to BMI, 74 (10.8%) according to BIA, and 127 (18.4%) following the skinfolds and circumferences assessments. There was no significant association between TMD-pain and obesity according to BMI (P = 0.95), BIA (P = 0.16), skinfold and circumference (P = 0.22), and neither with sedentarism (P = 0.94). Conclusion: Obesity and sedentarism were not associated with the presence of TMD-pain in adolescents.
Keywords: adolescents; body composition; body mass index; cross-sectional study; obesity; sedentarism; temporomandibular disorders